IMPLEMENTASI PERBANDINGAN MANAJEMEN MUTU PENDIDIKAN DI MAN INSAN CENDEKIA JAMBI DAN SMAN 1 PADANG PANJANG - Muhammad Rheza Nopriansa, K.A. Rahman, Verdianto, Servina Aida Putri, Sari Andri Yani, (Jurnal Tunas Pendidikan, 2023)
This study aims to provide insights related to education quality management or educational views to readers, observers, academics, and education practitioners to understand how the comparisons from various perspectives related to the quality of education are compared and also how the quality of education compares from one school to another. Then this research is also expected to raise public awareness of the importance of education, it is hoped that the quality of education in Indonesia can be better and continue to grow and improve. The results of this study are related to the quality of education at SMAN 1 Padang Panjang and MAN Insan Cendekia Jambi and it was found that these schools have good quality, it can be seen that in 2021 they will become the best schools through the results of the UTBK assessment, these schools have quality according to standards through optimizing functions and objectives. standardization, namely (1) as a basis for planning, implementing, and supervising education in the context of realizing quality national education, (2) guaranteeing the quality of national education in the context of educating the nation's life and shaping the character and civilization of a dignified nation, (3) National Education Standards refined in a planned, directed, and sustainable manner in accordance with the changing demands of local, national, and global life.